A Term Neonatal Case With Lethal Respiratory Failure Associated With a Novel Homozygous Mutation in ABCA3 Gene - Wei, Meili; Fu, Haibo; Han, Aiqin; Ma, Liji (Frontiers in Pediatrics, 2020)
The mutations in the ABCA3 (ATP-binding cassette transporter subfamily A member 3) gene could result in lethal respiratory distress syndrome (RDS) in neonates and interstitial lung disease (ILD) in infants and children. Here, we describe a full-term newborn who manifested respiratory distress 20 min after birth and then gradually developed hypoxemic respiratory failure and died on 53 days of life. A homozygous missense mutation (c.746C >T) was identified in exon 8 of ABCA3 gene in the neonate by next-generation sequencing, and the mutations were inherited from parents, respectively. This homozygous mutation is the first reported to date.